Genetic variability for vigor and yield of robusta coffee (Coffea canephora) clones in Ghana. Issue 8 (August 2022) - Akpertey, Abraham; Anim-Kwapong, Esther; Adu-Gyamfi, Paul Kwasi Krah; Ofori, Atta
Abstract: Effectiveness of plant improvement programs, especially in perennial crops like coffee, may be improved by knowing the level of genetic variation which exist within a breeding population coupled with the knowledge of estimates of genetic parameters for key agronomic traits. Thus, this study was conducted to evaluate C. canephora clones for growth (stem diameter, number of laterals and span) and yield traits; estimate genetic parameters of these traits; and determine the phenotypic and genetic associations between these traits to guide future crop improvement efforts. The productivity of 56 coffee clones was assessed from 2012 to 2020 in a clonal experiment planted in a randomized complete block design with three replicates. Each plot consisted of eight plants spaced at 2 × 3 m at the Cocoa Research Institute of Ghana. There were significant ( p < 0.001) differences among clones for all the traits assessed. Broad sense heritability was low-to-moderate for all the traits evaluated with the highest (0.34) observed for cumulative yield (CY). Cumulative yield was genetically correlated ( p < 0.001) with span and number of laterals (NOL). For the growth traits, NOL was the most strongly associated with CY ( r g = 0.49, p < 0.001). The results revealed that selection based on early years' yield (MY1) could be as effective as selection based on CY ( r g = 0.87, p < 0.001). Our findings indicate that there is significant genetic variation among the test clones for the parameters assessed and presents a good opportunity for future variety development. Abstract : Genetic correlation; Genetic parameters; Genetic variation; Germplasm; Heritability.